Automatized modeling of a human engineering simulation using Kinect. (February 2019) - Jun, Chanmo; Lee, Ju Yeon; Kim, Bo Hyun; Noh, Sang Do
Highlights: Traditional way of digital human modeling takes too much time, and its accuracy depends on the modeling technicians. An automated digital human modeling system using multiple depth cameras. Data model to combine and integrate the skeleton data from depth cameras through VRPN (Virtual Reality Peripheral Network). Easy and accurate generation of digital human model with low costs and time. Abstract: Many researchers of human engineering seek to enhance work efficiency and to reduce workloads by analyzing worker load, work efficiency, and production using analogue methods, such as checklists. Recent analyses have examined job performance using digital human models created by digitally recording the movements of actual workers through keyboard and mouse-based data input. However, this modeling method has two problems: it takes too much time to model all movements, and accuracy depends on the modeling technician. To solve these problems, this study presents a digital human modeling automation system using Kinect, a Microsoft Xbox data input device, to model human movements. The system is designed to utilize multiple Kinects, and the data model conveys and manages data from these devices to calibrate an algorithm that can be used to create a digital human model. Through this system, it is possible to easily generate a digital human model accurately, inexpensively, and efficiently. The developed digital human modeling automation system is verified using four scenarios, and the results, limitations, and development plan of the study are described.